Immunomodulatory effects of intestinal lung axis microecology and other factors on the prognosis of advanced non-small cell lung cancer - Shen, Changxing; Ren, Yanbei; Zhang, Xu; Xia, Qing; Li, Ming; Wang, Changhui; Fan, Lihong (Translational Cancer Research; Vol 8, No 5 (September 30, 2019): Translational Cancer Research, 2019)
Overall survival (OS) of lung cancer varies greatly with individual patients in the global setting. Multiple factors may affect the prognosis. Different antibiotics have significant effects on the prognosis of lung cancer patients. The intestinal microbiome, nutritional status and inflammatory factors all have significant impact on OS of lung cancer patients.